SOCIO-ETHICAL ASPECTS OF THE DEVELOPMENT OF ARTIFICIAL INTELLIGENCE AND THEIR SYNERGISTIC NATURE (World Bulletin of Social Sciences, 2026)
This article analyzes the socio-ethical aspects of the development of artificial intelligence and their synergistic nature. The rapid development of artificial intelligence technologies in modern society is leading to the transformation of social systems, the formation of new relationships between humans and technology. This process is considered from the point of view of synergism as a complex, self-organizing system. The article reveals the impact of artificial intelligence on moral norms, value systems and social relations in society. The social consequences of the development of artificial intelligence are also analyzed based on synergetic categories such as chance and necessity, order and chaos, stability and instability